Analysis of the effects of multiple injection strategies with hydrogen on engine performance and emissions in diesel engine - Gürbüz, Hüseyin (PERGAMON-ELSEVIER SCIENCE LTD, 2020)
In this study, firstly, the turbocharged, compression-ignition, light duty vehicle engine was loaded with a DC dynamometer. The real test engine was run at partial load (90%) and at different engine speeds with normal diesel fuel. In the second stage, a model engine was created and verified with the mixing control combustion (MCC) module suitable for hydrogen combustion using AVL BOOST simulation software with real test parameters such as engine performance and cylinder pressure values. At the last stage, multiple hydrogen injection strategies were applied in the simulation program using pure hydrogen as pilot and post fuel and diesel as the main fuel, and were examined numerically in terms of performance and emissions. The results showed that 2 pilot injections and 1 postinjection strategy reduced soot emissions more than 1 pilot injection strategy. However, NOx increased slightly in all three injection applications. In addition, a significant increase in engine power was observed. (C) 2020 Hydrogen Energy Publications LLC. Published by Elsevier Ltd. All rights reserved.
Keywords: Hydrogen; Pilot injection; NOx Soot emission; Heat release rate; Diesel engine